2001
DOI: 10.1073/pnas.101086398
|View full text |Cite
|
Sign up to set email alerts
|

Mirror self-recognition in the bottlenose dolphin: A case of cognitive convergence

Abstract: The ability to recognize oneself in a mirror is an exceedingly rare capacity in the animal kingdom. To date, only humans and great apes have shown convincing evidence of mirror self-recognition. Two dolphins were exposed to reflective surfaces, and both demonstrated responses consistent with the use of the mirror to investigate marked parts of the body. This ability to use a mirror to inspect parts of the body is a striking example of evolutionary convergence with great apes and humans.T he capacity for mirror… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
341
0
7

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 552 publications
(366 citation statements)
references
References 33 publications
12
341
0
7
Order By: Relevance
“…If not, it would suggest that the VENs may be related to behavioral specializations common to hominids, whales, and elephants. One such behavioral specialization could be mirror selfrecognition (Reiss and Marino, 2001;Plotnik et al, 2006). However, this awaits confirmation from further studies.…”
Section: Discussionmentioning
confidence: 99%
“…If not, it would suggest that the VENs may be related to behavioral specializations common to hominids, whales, and elephants. One such behavioral specialization could be mirror selfrecognition (Reiss and Marino, 2001;Plotnik et al, 2006). However, this awaits confirmation from further studies.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a number of cetacean species within the Delphinid family, including the common dolphin, share several behavioral and social characteristics with great apes and humans (Marino, 2002). Recently, Reiss and Marino (2001) showed that the bottlenose dolFigs. 20 -28.…”
Section: Discussionmentioning
confidence: 99%
“…Only human primates, chimpanzees, orangutans, and some bonobos, elephants, and dolphins have been shown to exhibit spontaneous mirror-guided selfexploration-e.g., self-directed behaviors such as examining body parts only visible in the mirror (for reviews, see Bard, Todd, Bernier, Love & Leavens, 2006;Gallup et al, 2002; also see Plotnik, de Waal & Reiss, 2006;Reiss & Marino, 2001). The aforementioned primates also pass the more formal "mark test" and will touch a red dot that has been inconspicuously applied to their brow or forehead.…”
Section: -Mirror Self-face Recognition (A) Msr and Self-awarenessmentioning
confidence: 99%